Genomic and phenotypic analyses of diverse non-clinical Acinetobacter baumannii strains reveals strain-specific virulence and resistance capacity. Issue 2 (15th February 2022) - Hamidian, Mohammad; Maharjan, Ram P.; Farrugia, Daniel N.; Delgado, Natasha N.; Dinh, Hue; Short, Francesca L.; Kostoulias, Xenia; Peleg, Anton Y.; Paulsen, Ian T.; Cain, Amy K.
Abstract : Acinetobacter baumannii is a critically important pathogen known for its widespread antibiotic resistance and ability to persist in hospital-associated environments. Whilst the majority of A. baumannii infections are hospital-acquired, infections from outside the hospital have been reported with high mortality. Despite this, little is known about the natural environmental reservoir(s) of A. baumannii and the virulence potential underlying non-clinical strains. Here, we report the complete genome sequences of six diverse strains isolated from environments such as river, soil, and industrial sites around the world. Phylogenetic analyses showed that four of these strains were unrelated to representative nosocomial strains and do not share a monophyletic origin, whereas two had sequence types belonging to the global clone lineages GC1 and GC2. Further, the majority of these strains harboured genes linked to virulence and stress protection in nosocomial strains. These genotypic properties correlated well with in vitro virulence phenotypic assays testing resistance to abiotic stresses, serum survival, and capsule formation. Virulence potential was confirmed in vivo, with most environmental strains able to effectively kill Galleria mellonella greater wax moth larvae. Using phenomic arrays and antibiotic resistance profiling, environmental and nosocomial strains were shown to have similar substrate utilisation patterns although environmental strains were distinctly more sensitive to antibiotics. Taken together, these features of environmental A. baumannii strains suggest the existence of a strain-specific distinct gene pools for niche specific adaptation. Furthermore, environmental strains appear to be equally virulent as contemporary nosocomial strains but remain largely antibiotic sensitive.